PEMBERDAYAAN KADER POSYANDU DALAM PROGRAM PENCEGAHAN STUNTING PADA BALITA DI MASA PANDEMI COVID-19 - Syarifah Has, Dwi Faqihatus (Indonesian Journal of Community Dedication in Health (IJCDH), 2021)
According to the results of Basic Health Research Indonesia stunting prevelansi in 2018 as much as 30.8%, 2019 as much as 27.67%, and still not meeting the national target in the number of stunting decreases. In Kutisari, the prevalence of clowns and stunting toddlers in the region is still relatively high because it has not met the minimum limit of stunting prevalence according to who is <20%. The purpose of this community service activity is the empowerment of posyandu cadres in order to prevent stunting during the COVID-19 pandemic is needed. This activity is conducted in 8 stages: 1) Situation Analysis, (2) Discussion on Solving Health Problems, (3) Socialization to Posyandu Cadres on health services by implementing strict health protocols, (4) Socialization of appropriate and effective methods in online provision (Wa) Group or other social media), (5) Training on making educational videos (6) Training in making leaflets, pocketbooks or other print media as a medium of assistance in providing education to stunting toddler mothers, (7) Healthy Food Product Development (8) Monitoring and evaluation of Community Service Activities. From the results of monitoring and evaluation, it was concluded that posyandu cadres better understand and get a lot of knowledge about stunting prevention counseling and safe, comfortable and effective educational methods during the Covid-19 pandemic. It is expected that this community service activity can run continuously so that it benefits the community. Keywords : Empowerment of Posyandu Cadres, Stunting Prevention, Covid-19 Pandemic